2017
DOI: 10.1097/qad.0000000000001269
|View full text |Cite
|
Sign up to set email alerts
|

Criminal justice involvement history is associated with better HIV care continuum metrics among a population-based sample of young black MSM

Abstract: Objective To examine how history of criminal justice involvement (CJI) is related to HIV care continuum metrics among young Black men who have sex with men (YBMSM) 16–29 years of age. Design Population-based survey Methods From 2013–2014 a representative sample of YBMSM was generated using Respondent Driven Sampling (RDS) in Chicago (n=618). HIV antibody/Ag and RNA testing were performed using dry blood spots. Factors assessed in the care continuum included HIV testing, HIV diagnosis, linkage-to-care withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
3
23
1
Order By: Relevance
“…The majority of enrolled CJI Black male participants were BMSM with limited education, income, and health insurance which is consistent with the literature on the impact of incarceration among BMSM and low socio-economic and health insurance status among CJI populations in the United States (14,(19)(20)(21). Overall, the current study found that the majority of CJI Black male participants reported low levels of stigma, high levels of social support, and minimal depressive symptoms.…”
Section: Characteristics Of Cji Black Men Enrolled In Lrisupporting
confidence: 88%
See 2 more Smart Citations
“…The majority of enrolled CJI Black male participants were BMSM with limited education, income, and health insurance which is consistent with the literature on the impact of incarceration among BMSM and low socio-economic and health insurance status among CJI populations in the United States (14,(19)(20)(21). Overall, the current study found that the majority of CJI Black male participants reported low levels of stigma, high levels of social support, and minimal depressive symptoms.…”
Section: Characteristics Of Cji Black Men Enrolled In Lrisupporting
confidence: 88%
“…Participants may be unsure about and/or are still assessing their current HIV care barriers at enrollment. The majority of participants did not report any drug use in the last month which is contrary to previous studies which have shown higher levels of drug use among CJI BMSM populations prior to and post incarceration (14,20,44). This is a high priority sample for HIV care and treatment interventions as most participants were not virally suppressed at baseline (56%) and had not achieved DVS (80%) over a 12-month period.…”
Section: Characteristics Of Cji Black Men Enrolled In Lricontrasting
confidence: 82%
See 1 more Smart Citation
“…Care cascade reports were available from the United States[49,50*,53,54,76,77]; Canada[51*]; the United Kingdom[55]; Nigeria[58]; Burkina Faso and Togo[56]; Russia[57]; and India[52]. MSM living with HIV in Burkina Faso and Togo, Russia, and India had alarmingly low levels of status awareness (18, 20 and 44%, respectively).…”
Section: Cascade Outcomes In Key Populationsmentioning
confidence: 99%
“…CBOs = community-based organizations High incarceration rates have also been documented among BMSM and persons living with HIV (PLWH) in the US [29][30][31][32][33][34][35]. For example, a six-city study of BMSM in the US found that 60% of participating BMSM reported a prior history of incarceration [30].…”
Section: Overall Partnership Structure Of La Iccsschmentioning
confidence: 99%